Analisis Piutang Pada PT. SUCOFINDO (Persero) Cabang Medan - Saputra, Raihan; Ramadani, Sri (Universitas Labuhanbatu, 2023)
In the midst of intense business competition, companies are required to be able to dominate the market, so companies need to carry out a credit sales strategy so that the number of sales increases. In general, receivables arise due to sales transactions of goods or services on credit. Investments that are too large in receivables can lead to slow turnover of working capital, so that the company's ability to increase sales volume becomes smaller. As a result, the smaller the opportunity the company has to make a profit or profit. The objective that is expected to be achieved from this research is to analyze bad debts made by PT. SUCOFINDO (Persero) Medan Branch. The analytical method used in this study is descriptive analysis to discuss problems that are described, described, compared, a data or situation, describe and explain the results of the research so that conclusions can be drawn. PT. SUCOFINDO (Persero) Medan Branch has performed receivables management and receivables analysis properly. Receivables that are past due 0 - 180 days and receivables that are 181 - 365 days old can be billed properly. Meanwhile, receivables that are > 1 year old are categorized as bad debts which will be set aside as uncollectible accounts.